2011
DOI: 10.1117/1.3533321
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid luminescent/magnetic nanostructured porous silicon particles for biomedical applications

Abstract: Abstract. This work describes a novel process for the fabrication of hybrid nanostructured particles showing intense tunable photoluminescence and a simultaneous ferromagnetic behavior. The fabrication process involves the synthesis of nanostructured porous silicon (NPSi) by chemical anodization of crystalline silicon and subsequent in pore growth of Co nanoparticles by electrochemically-assisted infiltration. Final particles are obtained by subsequent sonication of the Co-infiltrated NPSi layers and conjugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Also a non-superparamagnetic behavior has been observed for Co deposited within porous silicon particles, but all samples show a low coercivity [62] which indicates a low dispersion of Co within the porous structure offering only weak magnetic crosstalk.…”
Section: Magnetic Response Of Metal Filled Microporous Siliconmentioning
confidence: 82%
See 1 more Smart Citation
“…Also a non-superparamagnetic behavior has been observed for Co deposited within porous silicon particles, but all samples show a low coercivity [62] which indicates a low dispersion of Co within the porous structure offering only weak magnetic crosstalk.…”
Section: Magnetic Response Of Metal Filled Microporous Siliconmentioning
confidence: 82%
“…In contrast to the findings above, quenching of the photoluminescence has been reported after Co electrodeposition within porous silicon due to oxidation of the emitting centers. An additional blue emission band around 490 nm occurs due to silanol formation at the surface [62].…”
Section: Optical Properties Of Microporous Siliconmentioning
confidence: 99%
“…Moreover, cytotoxicity assays in human mesenchymal stem cells confirmed that porous silicon-based microand nanoparticles do not induce apoptosis. 24 Accordingly, the definition of Si/nanoPS surface patterns at microscale level leads to simultaneous chemical and nanotopographic contrasts, which will be subsequently used for the control of cell adhesion and migration.…”
Section: Resultsmentioning
confidence: 99%
“…From the point of view of the development of drug-delivery applications, nanoPS is a material able to carry biomolecules conjugated to drugs for achieving site-specific delivery, thus making nanoPS microparticles suitable candidates for the development of novel drug delivery systems [9][10][11]. However, in most cases the drug does not enter the pores, being then necessary to functionalize the surface of nanoPS.…”
Section: Introductionmentioning
confidence: 99%